2016
DOI: 10.1159/000438619
|View full text |Cite
|
Sign up to set email alerts
|

Role of ALKBH1 in the Core Transcriptional Network of Embryonic Stem Cells

Abstract: Background/Aims: ALKBH1, an AlkB homologue in the 2-oxoglutarate and Fe2+ dependent hydroxylase family, is a histone dioxygenase that removes methyl groups from histone H2A. Studies of transgenic mice lacking Alkbh1 reveal that most Alkbh1-/- embryos die during embryonic development. Embryonic stem cells (ESCs) derived from these mice have prolonged expression of pluripotency markers and delayed induction of genes involved in neural differentiation, indicating that ALKBH1 is involved in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…Interestingly, previous reports have suggested a differential localisation of ABH1 in different cell types. While the dioxygenase is mainly localised in mitochondria and the cytoplasm in HEK293 and HeLa cells ( Fig 5; Westbye et al, 2008), it has been reported to be nuclear in embryonic stem cells (Ougland et al, 2012(Ougland et al, , 2016. Together, these findings suggest that the methylation of cytosine 34 in mt-tRNA Met by NSUN3 represents an important modification present in many, if not all cell types, while the different localisation of ABH1 might result in differential modification of mt-tRNA Met on cytosine 34 in different cell types, tissues and developmental stages and might thereby fine tune mitochondrial translation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous reports have suggested a differential localisation of ABH1 in different cell types. While the dioxygenase is mainly localised in mitochondria and the cytoplasm in HEK293 and HeLa cells ( Fig 5; Westbye et al, 2008), it has been reported to be nuclear in embryonic stem cells (Ougland et al, 2012(Ougland et al, , 2016. Together, these findings suggest that the methylation of cytosine 34 in mt-tRNA Met by NSUN3 represents an important modification present in many, if not all cell types, while the different localisation of ABH1 might result in differential modification of mt-tRNA Met on cytosine 34 in different cell types, tissues and developmental stages and might thereby fine tune mitochondrial translation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the species, particular ALKBH proteins show diverse cellular localization, substrate specificity, and the ability to interact with other proteins . Here, we compare functions of ALKBH proteins present in higher eukaryotes of distinct taxons—mammals, especially H. sapiens and higher plant like A. thaliana .…”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
“…It also influences translation by mediating the demethylation of 1‐meA on tRNA . Finally, ALKBH1 interacts with transcription factors of pluripotency and is involved in its regulation and differentiation . Other studies indicate that ALKBH1 protein, independent of dioxygenase domain, possesses DNA lyase activity .…”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%
See 1 more Smart Citation
“…Cultured ES cells have three characteristics in vitro : self-renewal, pluripotency and limitless proliferation [3, 4]. The self-renewal of mouse ES cells maintained by activating pluripotent-related signalling pathways or inhibiting differentiation-related signalling pathways [5-7]. Some small molecule modulators maintain the undifferentiated and pluripotent state of mouse ES cells by affecting different signalling pathways.…”
Section: Introductionmentioning
confidence: 99%